Does Inflammation Determine Whether Obesity Is Metabolically Healthy or Unhealthy? The Aging Perspective. (4th October 2012) - Alam, Iftikhar; Ng, Tze Pin; Larbi, Anis
Abstract : Obesity is a major health issue in developed as well as developing countries. While obesity is associated with relatively good health status in some individuals, it may become a health issue for others. Obesity in the context of inflammation has been studied extensively. However, whether obesity in its various forms has the same adverse effects is a matter of debate and requires further research. During its natural history, metabolically healthy obesity (MHO) converts into metabolically unhealthy obesity (MUHO). What causes this transition to occur and what is the role of obesity-related mediators of inflammation during this transition is discussed in this paper.